Assessment of rotahaler inhalation technique among patients with chronic obstructive pulmonary disease in a teaching hospital of Nepal - Sapkota, Diksha; Amatya, Yogesh Raj (Journal of Kathmandu Medical College, 2017)
Background: Inhalation mode of drug delivery is the mainstay treatment for chronic obstructive pulmonary disease, however; incorrect technique prevents patients from receiving maximal therapeutic benefi ts. Objectives: To assess usage technique of rotahaler among patients with chronic obstructive pulmonary disease and identify factors affecting its performance. Methods: Descriptive cross sectional study was conducted to assess rotahaler (single unit dose dry powder inhaler) inhalation technique among patients with chronic obstructive pulmonary disease in Kathmandu University Teaching Hospital. The study population consisted of 100 respondents using rotahaler for at least one year. Data collection was done by standard checklist, semi structured questionnaire via observation and interview methods respectively. Results: Correct inhalation technique was found in 37% of total respondents. Nearly two out of three respondents (61%) failed to breathe out deeply before inhaling. Majority of the respondents (59%) failed to hold breath for at least 10 second and 25% were unable to breathe in deeply. Age, occupation, source of inhalation instruction and re-demonstration of the technique were found to be signifi cantly associated with the correct inhalation technique (p <0.05). Conclusion: More than half of the respondents had incorrect inhalation technique, so health education program targeting the common identifi ed errors should be carried out. Arrangements should be made for regular involvement of pharmacist in teaching and re-demonstration to ensure good inhaler technique. This would ultimately lead to a greater clinical response and improved patient compliance. Journal of Kathmandu Medical College Vol. 5, No. 1, Issue 15, Jan.-Mar., 2016, Page: 11-17